(untitled) (Grande Medical Journal, 2021)
A 65-year-old lady, admitted to ICU for septic shock, underwent left radial artery cannulation with 20G cannula for hemodynamic monitoring. She was on mechanical ventilation for severe community acquired pneumonia and was treated with antibiotics and vasopressors (noradrenaline and vasopressin). On the fourth day of arterial cannulation, she developed bluish discoloration of her left hand and digits (Figure 1a), associated with coldness and impaired capillary refill. The other hand did not show any features of compromised circulation. Ultrasonography of left radial artery revealed intraluminal thrombus and absence of color flow in color Doppler (Figure 1b). The radial catheter was removed and she received therapeutic dose of enoxaparin. She expired three days later due to refractory shock.